Bilateral slipped capital femoral epiphysis in a cerebral palsy patient: a Case Report - Abdulmonem M. Alsiddiky; Musab Alageel; Abdulaziz Alsubaie; Malak N. AlShebel (BMC Musculoskeletal Disorders)
Abstract Background Slipped capital femoral epiphysis (SCFE) is usually seen in patients with high body mass index (BMI) and endocrine diseases. SCFE is exceedingly rare among Cerebral palsy (CP) patients due to spasticity present in those patients. Percutaneous in situ fixation is the treatment option for SCFE patients. According to the literature, there’s no single case report with SCFE in a spastic CP patient with no prior history of trauma, seizure episodes, or endocrine disease. Case presentation We report a case of an 11-year-old spastic cerebral palsy (CP) patient with a physical status of level 5 motor function on the gross motor function classification system. He was brought by his mother to the clinic complaining of bilateral hip pain. The mother denied any history of trauma or any seizure episodes. The pain had started spontaneously. Physical examination showed severe spasticity and bilateral hip abduction with external rotation. Drehmann’s sign was positive. Bilateral hip radiographs revealed bilateral partial open femoral capital physis with evidence of SCFE bilaterally. Also, the Southwick angle was measured, and it was severe. The patient was taken to the operating room and treated with closed reduction and percutaneous in situ fixation. He was seen multiple times following surgical intervention, reporting pain relief, and showing complete wound healing. Conclusion This report concludes that paraplegic spastic CP patients may present with SCFE spontaneously without trauma, seizures, or an underlying endocrine disease. Also, severe spasticity might potentially be a risk factor for SCFE, although further investigations would be necessary to establish a conclusive link.